The Implementation of “WHATSAPP” as a Media of English Language Teaching - Kheryadi Kheryadi (Loquen, 2017)
This paper discusses the implementation of WhatsApp as one of the current beneficial devices to assist students in communicative language learning. It allows them to engage actively in online conversation and create confidence to use English in daily communication through two forms of conversation such as independent and dependent conversation. The first type assists students in interacting among themselves to discuss curios interesting topics, whereas teachers are not involved in their online dialogues. The later, however, acquire, teacher to guide the whole processes, and they are actively participating in the online discussion. This media can help students build their confidence and motivation to learn. Based on the question are distributed to the subject, it revealed that they felt confident, independence, enthusiasm, and having a positive attitude to learn English using application, hence, WhatsApp is one of the recent technologies that can be used in language teaching.